CRITICAL REVIEW OF BHAVPRAKASH NIGHANTU WITH SPECIAL REFERENCE TO PHARMACOVIGILANCE PERSPECTIVE OF MEDICINAL PLANTS AND ITS PRACTICAL APPLICATION IN THERAPEUTICS - Prajapati, Jaynam; Lukhi, Janki; Bapna, Vidhi (Journal of Ayurvedic Herbal and Integrative Medicine, 2024)
Introduction: Ayurveda is ancient literature for protecting the health of healthy individual and curing the diseased one. With this aim in World-wide Ayurveda has increased in their practice in form of diets, medicine and routines. As increasing use in western countries, it leads to concern of regarding safety of use. There are various publications which raise concern about the safety of Ayurveda medicines. Today Ayurveda is gathering globally attention with regards to therapeutic option to treat various acute, chronic and non-infectious diseases. Though Ayurveda is practiced for centuries, there is a few of systematic documentation regarding adverse drug reactions (ADRs) occurrence after administration of Aushadha and safety of Aushadha (Ayurvedic medicine). For safety and efficacy of Aushadha, systematic documentation related to ADR’s mentioned in different Samhitas. With respect to Bhavpraksha Nighantu mentioned various ADRs with drugs as mention of Aushadha is given amazing. Materials and Methods: Bhavprakasha Nighantu was studied critically to look for description of ADRs in medicinal plants (poisonous drugs were excluded) This ADRs were analysed and presented systemically. Result and Discussion: ADRs aims to achieve qualitative use of drugs and to achieve safety and therapeutic uses to treat with caution. The drugs selected from classics name Bhavprakash Nighantu and their adverse effect with respect to administration of drugs and complication. Use of drugs with safety and prevent ADRs in Ayurvedic medicines Conclusion: For Understanding the safety of use of Ayurvedic medicine is need in today era with the help of Pharmacovigilance study.